Novel Approaches in Cardiac Imaging for Non-invasive Assessment of Left Heart Myocardial Fibrosis - Mandoli, Giulia Elena; D'Ascenzi, Flavio; Vinco, Giulia; Benfari, Giovanni; Ricci, Fabrizio; Focardi, Marta; Cavigli, Luna; Pastore, Maria Concetta; Sisti, Nicolò; De Vivo, Oreste; Santoro, Ciro; Mondillo, Sergio; et al. (Frontiers in Cardiovascular Medicine, 2021)
In the past, the identification of myocardial fibrosis was only possible through invasive histologic assessment. Although endomyocardial biopsy remains the gold standard, recent advances in cardiac imaging techniques have enabled non-invasive tissue characterization of the myocardium, which has also provided valuable insights into specific disease processes. The diagnostic accuracy, incremental yield and prognostic value of speckle tracking echocardiography, late gadolinium enhancement and parametric mapping modules by cardiac magnetic resonance and cardiac computed tomography have been validated against tissue samples and tested in broad patient populations, overall providing relevant clinical information to the cardiologist. This review describes the patterns of left ventricular and left atrial fibrosis, and their characterization by advanced echocardiography, cardiac magnetic resonance and cardiac computed tomography, allowing for clinical applications in sudden cardiac death and management of atrial fibrillation.